A New Alternatıve For Molar Dıstausatıon "Magnetıc Forces - Eray Erdoğan; Semra Ciğer (Galenos Yayinevi, 1990)
The difficulties in application and in patient cooparation of classical treatment methods for the Class II Division 1 2 cases, directed the researchers to find new and more practical treatment methods. The use of magnetic forces in orthodontics appear to be a new alternative for the distalisation of upper posterior segments. For this reason, we used magnetic forces for distalisation of upper first molars to develop this method and to introduce this new treatment alternative to the Turkish Orthodontic Society. We distalised the upper first molars of three Cl II/1 cases being II years old-one of them was male, two of them were females-with the help of the samarium-cobalt magnents coated with stainless steel in six weeks. Appointments were regulated once in a week and results were recorded. We found out that upper first molars, migrated distally about "6mm"at the six weeks. On the other hand, we determined the position of the upper molars before and after the application of magnetic forces, with a cephalometric study by the linear measurements made from the Ricketts ptv Plane and we observed that upper first molars of three cases moved distally about "3.3mm" in six weeks. At the same time, we used Nasion-Basion cephalometric superpositions on point "C.C" to show schematically the distalisation op upper first molars.